2016
DOI: 10.1177/1471301216659771
|View full text |Cite
|
Sign up to set email alerts
|

Intimacy between care home residents with dementia: Findings from a review of the literature

Abstract: While studies of residents' expression of sexuality and their engaging in sexual behaviour with other resident(s) may be challenging to manage in care home settings and can be emotionally painful or uncomfortable for families, the review found that studies are few in number and span emotional intimacy and distressing behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 72 publications
(77 reference statements)
1
14
0
Order By: Relevance
“…Following the literature review (see Wiskerke & Manthorpe, 2016) the following research question was developed: what are the views of relatives and care workers of new relationships or sexual intimacy between care home residents with dementia, whilst married to their spouse? Full ethical approval was granted in 2015 by King's College London.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the literature review (see Wiskerke & Manthorpe, 2016) the following research question was developed: what are the views of relatives and care workers of new relationships or sexual intimacy between care home residents with dementia, whilst married to their spouse? Full ethical approval was granted in 2015 by King's College London.…”
Section: Methodsmentioning
confidence: 99%
“…A recent literature review investigated this subject and sought details of studies that had compared relatives and care workers' views (Wiskerke & Manthorpe, 2016). While some studies have explored the views of relatives (Bauer et al, 2014), greater number of studies have reported the views of care workers (Archibald, 1998;Ehrenfeld, Tabak, Bronner, & Bergman, 1997;Tzeng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Resource material and studies in the Indian context are however lacking, and would be of considerable importance in shaping policies. 13,15 Sexual Abuse in Dementia Elder abuse was defined by the WHO in 2002 as "a single, or repeated act, or lack of appropriate action, occurring within any relationship where there is an expectation of trust which causes harm or distress to an older person." 40 Sexual violence was further defined by the WHO in 2011 as "any sexual act, attempt to obtain a sexual act, unwanted sexual comments or advances, or acts to traffic or otherwise directed against a person's sexuality using coercion, by any person regardless of their relationship to the victim, in any setting, including but not limited to home and work."…”
Section: Sexuality and Residential Carementioning
confidence: 99%
“…The formation of new relationships in persons with dementia is often of greater concern than a preexisting relationship because it raises the question of consent, as discussed above. 15…”
Section: Dementia and The Formation Of A New Relationshipmentioning
confidence: 99%
“…There are other issues that need to be considered, such as sexual functioning in sexual and gender minorities 34 in older adults. The nature of consent to sexual intimacy in older adults with cognitive impairment and in long-term care facilities 35 also merit discussion. These have not been addressed because they were considered to be out of the scope of the present discussion.…”
Section: Other Issuesmentioning
confidence: 99%